Candesartan could ameliorate the COVID-19 cytokine storm (2020)
Background: Angiotensin receptor blockers (ARBs) reducing inflammation and protecting lung and brain function, could be of therapeutic efficacy in COVID-19 patients. Methods: Using GSEA, we compared our previous transcriptome analysis of neurons injured by glutamate and treated with the ARB Candesartan (GSE67036) with transcriptional signatures from SARS-CoV-2 infected primary human bronchial epithelial cells (NHBE) and lung postmortem (GSE147507), PBMC and BALF samples (CRA002390) from COVID-19 patients. Results: Hundreds of genes upregulated in SARS-CoV-2/COVID-19 transcriptomes were similarly upregulated by glutamate and normalized by Candesartan. Gene Ontology analysis revealed expression profiles with greatest significance and enrichment, including proinflammatory cytokine and chemokine activity, the NF-kappa B complex, alterations in innate and adaptive immunity, with many genes participating in the COVID-19 cytokine storm. Conclusions: There are similar injury mechanisms in SARS-CoV-2 infection and neuronal injury, equally reduced by ARB treatment. This supports the hypothesis of a therapeutic role for ARBs, ameliorating the COVID-19 cytokine storm.